Gelatinase Biosensor Reports Cellular Remodeling During Epileptogenesis - Bouquier, Nathalie; Girard, Benoit; Aparicio Arias, Juri; Fagni, Laurent; Bertaso, Federica; Perroy, Julie (Frontiers in Synaptic Neuroscience, 2020)
Epileptogenesis is the gradual process responsible for converting a healthy brain into an epileptic brain. This process can be triggered by a wide range of factors, including brain injury or tumors, infections, and status epilepticus. Epileptogenesis results in aberrant synaptic plasticity, neuroinflammation and seizure-induced cell death. As Matrix Metalloproteinases (MMPs) play a crucial role in cellular plasticity by remodeling the extracellular matrix, gelatinases (MMP-2 and MMP-9) were recently highlighted as key players in epileptogenesis. In this work we engineered a biosensor to report in situ gelatinase activity in a model of epileptogenesis. This biosensor encompasses a gelatinase-sensitive Activatable Cell Penetrating Peptide (ACPP) coupled to a TAMRA fluorophore, allowing fluorescence uptake in cells displaying endogenous gelatinase activities. In a preclinical mouse model of temporal lobe epilepsy, the intrahippocampal kainate injection, ACPPs revealed a localized distribution of gelatinase activities, refining temporal cellular changes during epileptogenesis. The activity was found particularly but not only in the ipsilateral hippocampus, starting from CA1 area and spreading to dentate gyrus from the early stages throughout chronic epilepsy, notably in neurons and microglial cells. Thus, our work shows that ACPPs are suitable molecular imaging probes for detecting spatiotemporal pattern of gelatinase activity during epileptogenesis, suggesting their possible use as vectors to target cellular reactive changes with treatment for epileptogenesis.